2021
DOI: 10.4093/dmj.2020.0185
|View full text |Cite
|
Sign up to set email alerts
|

Trends and Risk Factors of Metabolic Syndrome among Korean Adolescents, 2007 to 2018

Abstract: Background: There is a lack of recent research on the changes in risk factors for metabolic syndrome (MetS) in the Asian pediatric population. We aimed to determine the 12-year trends in the prevalence of MetS and relevant lifestyle factors such as smoking, exercise, and calorie intake among Korean adolescents. Methods: We investigated trends in MetS and lifestyle factors among 6,308 adolescents aged 12 to 18 years from the Korea National Health and Nutrition Examination Survey, 2007 to 2018. Results: The prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 47 publications
1
10
1
Order By: Relevance
“…In this article, entitled “Trends and risk factors of metabolic syndrome among Korean adolescents, 2007 to 2018” [ 4 ], the rate of metabolic syndrome among adolescents aged 12 to 18 years did not change significantly from 1.7% in 2007 to 2.2% in 2018. However, during that period, the components of metabolic syndrome showed statistically significant changes (abdominal obesity, 8.1% to 11.2%; hyperglycemia, 5.3% to 10.4%; hypo-high density lipoprotein-cholesterolemia, 22.4% to 14.8%).…”
mentioning
confidence: 99%
“…In this article, entitled “Trends and risk factors of metabolic syndrome among Korean adolescents, 2007 to 2018” [ 4 ], the rate of metabolic syndrome among adolescents aged 12 to 18 years did not change significantly from 1.7% in 2007 to 2.2% in 2018. However, during that period, the components of metabolic syndrome showed statistically significant changes (abdominal obesity, 8.1% to 11.2%; hyperglycemia, 5.3% to 10.4%; hypo-high density lipoprotein-cholesterolemia, 22.4% to 14.8%).…”
mentioning
confidence: 99%
“…We want to thank Dr. Dae Jung Kim for his interest in and critical comments on our recent paper, “Trends and risk factors of metabolic syndrome among Korean adolescents, 2007 to 2018” [ 1 ]. We also appreciate the opportunity to respond to Dr. Dae Jung Kim’s letter submitted to the Diabetes and Metabolism Journal .…”
mentioning
confidence: 99%
“…In this study, a decreasing rate of smoking among Korean adolescents over a span of 12 years was noted. In addition, controversial findings have shown that adolescent smokers have lower fasting blood sugar levels [ 1 ]. Although the data were not included in this study, smoking was not significantly associated with the overall odds of metabolic syndrome in our study population.…”
mentioning
confidence: 99%
“…
Recent studies implied that an increase in calorie consumption and a decrease in physical activity among Korean teenagers contributed to an in central obesity, dyslipidemia, metabolic syndrome, and type 2 diabetes over the last decade. [1][2][3][4][5][6][7] Obesityrelated insulin resistance is a key pathophysiology of diabetes development. 8) Various insulin resistance indices, such as Homeostasis Model Assessment for Insulin Resistance, insulin sensitivity index, triglyceride to high-density lipoprotein-cholesterol ratio, and triglyceride and glucose index have been proposed to identify and stratify insulin resistance in obese populations and to aid in the early detection and prevention of type 2 diabetes mellitus.
…”
mentioning
confidence: 99%
“…Recent studies implied that an increase in calorie consumption and a decrease in physical activity among Korean teenagers have contributed to an increase in central obesity, dyslipidemia, metabolic syndrome, and type 2 diabetes over the last decade [ 1 - 7 ]. Obesity-related insulin resistance is a key pathophysiology of diabetes development [ 8 ].…”
mentioning
confidence: 99%